P017 Out of outlier status: local observations from the National Early Inflammatory Arthritis Audit. (26th April 2021) - MacPhie, Elizabeth; Ashcroft, Lesley; Brazendale, Jane; Foreman, Nicola; Gilbert, Sharon; Greenall, Carol; Horton, Sarah; Lewis, Irene; Madan, Ayesha; Rao, Chandini; Fish, Sarah
Abstract: Background/Aims   The National Early Inflammatory Arthritis Audit (NEIAA) provides a powerful lever for driving up quality. Rheumatology services benchmark care against NICE quality standards (QS) 33. Notifications are sent out quarterly to Trusts at risk of being an outlier and outliers are identified in the annual report. After being named as an outlier, this project describes our journey to improve compliance against QS2 (patients are seen in a rheumatology clinic within 3 weeks of referral and QS3 (patients with rheumatoid arthritis (RA) are started on DMARDs within 6 weeks of referral). Methods   Data submitted to the NEIAA online tool during year one were downloaded for analysis. Results were presented to the Rheumatology Multi-Disciplinary Team, the patient pathway was mapped, driver diagrams were developed by the team and areas for improvement identified and changes implemented. Data from year two were downloaded for comparison. Results   In total 530 patients were recruited to the audit: 262 in year 1 and 268 in year 2. 77 (29%) in year 1 and 73 (27%) in year 2 had confirmed RA and were included in this analysis. All patients had a baseline form completed, and 61 (86%) and 56 (77%) had a 3-month follow-up form completed for year 1 and 2, respectively. The demographics were very similar for years 1 and 2. In year 1, 10% of all patients were seen within 3 weeks of being referred and 7% in the RA cohort started DMARD therapy within 6 weeks of referral. This compared to 54% and 56%, respectively, in year 2. Changes implemented relating to QS2 included referral guidelines for primary care, prompts when requesting rheumatoid factor and CCP antibodies and changes to the wording of antibody reports, increased triage capacity, simplifying the booking process and increased new appointment capacity (additional consultant, upskilling extended scope practitioner). QS3 changes implemented included increasing drug education and monitoring clinic capacity and improved sign-posting to National Rheumatoid Arthritis Society. Initial combination therapy was more prevalent in sero-positive patients and those with a high DAS28 during both years. In year 1, disease activity at baseline vs. 3 months was: remission/low disease activity in 8% vs. 54%, moderate in 45% vs. 39% and high in 47% vs. 7%. In year 2, rates at baseline vs. 3 months were: remission/low disease activity 12% vs. 69%, moderate in 60% vs. 25% and high in 28% vs. 6%. Conclusion   Significant changes have been made which have resulted in an improvement in performance against QS2 and 3. Disease activity at baseline was lower, potentially as a result of seeing patients sooner and this has resulted in better outcomes for patients at 3 months. Ongoing data collection will allow the team to determine outcomes at 12 months. Disclosure   E. MacPhie: Other; EM is the secretary of the North West Rheumatology Club, these regional meetings have been funding by an unrestricted educational grant from UCB and are now sponsored by Abbvie. L. Ashcroft: None. J. Brazendale: None. N. Foreman: None. S. Gilbert: None. C. Greenall: None. S. Horton: None. I. Lewis: None. A. Madan: None. C. Rao: None. S. Fish: None.